1999
DOI: 10.1021/jp984346w
|View full text |Cite
|
Sign up to set email alerts
|

A Coupled-Cluster Analysis of the Electronic Excited States in Aminobenzonitriles

Abstract: The excited states of 4-(N,N-dimethylamino)benzonitrile (DMABN) and 4-aminobenzonitrile (ABN) are characterized by the similarity transformed equation-of-motion coupled-cluster method with single and double excitations (STEOM-CCSD). The long wavelength band of DMABN is assigned by STEOM-CCSD to an emission of a geometrically relaxed twisted intramolecular charge transfer (TICT) state. In contrast, no lowering in total energy upon twisting is found in ABN. The different behavior of the TICT states in ABN and DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
64
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 39 publications
10
64
0
Order By: Relevance
“…32 Thus, the amino group becomes planar upon ionization, and the N-H bonds are calculated to slightly elongate from 1.0056 to 1.0115 Å. 15 The symmetric and antisymmetric N-H stretch fundamentals predicted at ν s NH = 3380 cm −1 and ν a NH = 3492 cm −1 are in good agreement with the measured values of 3390 and 3482 cm −1 , 15, 33 respectively.…”
Section: A Abn + -H 2 Omentioning
confidence: 61%
“…32 Thus, the amino group becomes planar upon ionization, and the N-H bonds are calculated to slightly elongate from 1.0056 to 1.0115 Å. 15 The symmetric and antisymmetric N-H stretch fundamentals predicted at ν s NH = 3380 cm −1 and ν a NH = 3492 cm −1 are in good agreement with the measured values of 3390 and 3482 cm −1 , 15, 33 respectively.…”
Section: A Abn + -H 2 Omentioning
confidence: 61%
“…6.04, 5.76, and 12.14 D were respectively obtained for the three states by CASSCF wave function (see Table 2). Borst et al reported 6 6.19 6.06 12.25 CASSCF Parusel et al 8 6.81 7.61 11.61 STEOM Borst et al 9 6.41 7.20 a -377.599556 au. b -377.601692 au.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Osawa et al recently reported Raman spectra of the CtN stretching vibration of ABN and its electronic absorption spectra in water, methanol, and cyclohexane under sub-and supercritical conditions as well as in acetonitrile under subcritical condition. 12 As the solvent density increases from the gaseous region to F r ) 1.5, where F r is the reduced density by the critical density of the solvent, the absorption peak positions in water and methanol decrease.…”
Section: Introductionmentioning
confidence: 99%
“…4ABN is known to be a push-pull molecule, with electron acceptor and donor substituents in para position on the aromatic benzene. Over the past few decades, many experimental 31 -37 and quantum chemical theoretical 38 studies, including the excited states of these molecules, 39,40 have been conducted on 4ABN.…”
Section: Introductionmentioning
confidence: 99%